Corrigendum to “Relationship between thermal environment, thermoregulatory responses and energy metabolism in goats: A comprehensive review” [Journal of Thermal Biology 109 (2022) 103324](S0306456522001383)(10.1016/j.jtherbio.2022.103324) - Lima, Ana Rebeca Castro [UNESP]; Silveira, Robson Mateus Freitas; Castro, Maria Samires Martins; Vecchi, Laura Bertolaso De; Souza Bahia, Angélica Santos Rabelo de [UNESP]; Melo, Thaise Pinto de [UNESP]; Fernandes, Márcia Helena Machado da Rocha [UNESP]; Resende, Kléber Tomás [UNESP] (Elsevier, 2023)
The authors regret that the names of two authors were missed in the original article - Angélica Santos Rabelo de Souza Bahia and Thaise Pinto de Melo. This corrigendum aims to correct this, and list the contribution of the authors as follows: Authors’ contributions Conceptualization: [A.R.C.Lima]; [RMF Silveira]; [M.S.M.Castro]; [A.S.R.S. Bahia]; [T.P. Melo]; [M. H. M. Da R. Fernandes]; [K.T. Resende]. Writing - preparing the original draft: [A.R.C.Lima]; [RMF Silveira]; A.S.R.S. Bahia]; [T.P. Melo]. Writing – review and editing; [A.R.C.Lima]; [RMF Silveira]; [MSM Castro] [LB De Vecchi] [A.S.R.S. Bahia]; [T.P. Melo]. Supervision: [M. H. M. Da R. Fernandes] [K.T. Resende]. All authors read and approved the manuscript. Figure credits A.R.C.Lima A.S.R.S. Bahia; T.P. Melo; The authors would like to apologise for any inconvenience caused.